10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
ObjectiveThis study aims to describe the clinical characteristics, multimodal management, and outcomes of SMARCB1 (INI-1)-deficient sinonasal carcinoma (SDSC) within a single-institution cohort.MethodsA retrospective descriptive study of 12 SDSC patients diagnosed between March 2019 and December 2024 was conducted. All patients received multimodal therapy, including surgery, radiotherapy, chemotherapy, and immunotherapy. Clinical outcomes evaluated included overall survival (OS), progression-free survival (PFS), and the response to neoadjuvant treatment.ResultsThe cohort consisted of 10 males (83%) and 2 females (17%), with a mean age of 37 years (range: 23-63). The ethmoid sinus was the most frequently involved site (7/12, 58%), and 10 patients (83%) presented with locally advanced T4 disease. Notably, immunotherapy (PD-1 blockade) was universally integrated into the multimodal continuum for all 12 patients at various disease stages. Among the nine patients who received neoadjuvant therapy, three (3/9) achieved an objective response, and all nine patients (9/9) achieved disease control prior to local consolidation. With a median follow-up of 30 months (range: 4-50), the median OS was 41 months. The 1-, 2-, 3-, and 4-year OS rates were 83%, 83%, 66%, and 22%, respectively. The median PFS was 34 months, with 1-, 2-, 3-, and 4-year PFS rates of 75%, 64%, 43%, and 43%, respectively.ConclusionOur findings suggest that integrating PD-1 blockade into multimodal treatment regimens is feasible and shows promising potential for disease control in SDSC. This descriptive series provides practical reference data and highlights a potential therapeutic avenue for future research.